2011
DOI: 10.1108/02630801111162350
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the costs of resilient reinstatement of flood affected properties

Abstract: Purpose -Recently, the focus of UK and European flood risk management policy has been towards promoting the uptake of property level flood adaptation measures. Despite this focus, the take-up of property level flood adaptation measures (both resilient and resistant) remains very low. One of the apparent barriers to uptake is the cost of installing such measures. This study aims to investigate the cost of adopting resilient reinstatement measures by considering a small number of actual properties that were floo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 9 publications
0
30
1
Order By: Relevance
“…Thurston et al, (2008) asserted that a key to reducing impacts of flooding on household is the take-up of property level flood risk adaptation measures both in new developments and as part of repair after flood events. Property level flood risk adaptation measures refer to all actions available to homeowners to adapt their properties to flood risk (Joseph et al, 2011b) and involves the process of adjustment of households behaviours to actual or expected flood risk in order to reduce its impacts on households (IPCC, 2012). These include collective process of either keeping water out -resistance measures or allowing the water into the property but reducing the damage caused to the fabric of the property -resilience measures (ABI, 2003, Thurston et al, 2008, Beddoes and Booth, 2011, Wassell et al, 2009, Joseph et al, 2011b, Warren et al, 2011, JBA, 2012, Royal Haskoning, 2012, thereby allowing quick reinstatement of the property after flood water has receded.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thurston et al, (2008) asserted that a key to reducing impacts of flooding on household is the take-up of property level flood risk adaptation measures both in new developments and as part of repair after flood events. Property level flood risk adaptation measures refer to all actions available to homeowners to adapt their properties to flood risk (Joseph et al, 2011b) and involves the process of adjustment of households behaviours to actual or expected flood risk in order to reduce its impacts on households (IPCC, 2012). These include collective process of either keeping water out -resistance measures or allowing the water into the property but reducing the damage caused to the fabric of the property -resilience measures (ABI, 2003, Thurston et al, 2008, Beddoes and Booth, 2011, Wassell et al, 2009, Joseph et al, 2011b, Warren et al, 2011, JBA, 2012, Royal Haskoning, 2012, thereby allowing quick reinstatement of the property after flood water has receded.…”
Section: Introductionmentioning
confidence: 99%
“…Property level flood risk adaptation measures refer to all actions available to homeowners to adapt their properties to flood risk (Joseph et al, 2011b) and involves the process of adjustment of households behaviours to actual or expected flood risk in order to reduce its impacts on households (IPCC, 2012). These include collective process of either keeping water out -resistance measures or allowing the water into the property but reducing the damage caused to the fabric of the property -resilience measures (ABI, 2003, Thurston et al, 2008, Beddoes and Booth, 2011, Wassell et al, 2009, Joseph et al, 2011b, Warren et al, 2011, JBA, 2012, Royal Haskoning, 2012, thereby allowing quick reinstatement of the property after flood water has receded. In addition, property can be adapted to flood risk by relocating expensive items from ground floor to upper floor or by registering for flood alert warning (Walker et al, 2008, Priest et al, 2008.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resilience measures aim to reduce the consequence of flooding by, for example, facilitating the early recovery of buildings, infrastructure or other vulnerable sites following a flood event (Joseph et al, 2011). Flood resilience measures reduce the cost of repairs after deep and prolonged floods, and can speed up restoration times.…”
Section: Figure 2: Percentage Of Residential Homeowners Who Had Implementioning
confidence: 99%
“…In a review of the international literature on resilience, the findings are grouped in terms of four barrier types: informational, financial, emotional and timing issues [8]; these, in turn, impacted variously on components within the decision making process such as the necessary awareness and perception of risk; ownership of the risk; knowledge of solutions; resources to implement solutions (including financial issues); and belief that the measures would work. It has been found that, although resilient reinstatement did cost more than traditional repair, this approach did significantly reduce future repair costs (assuming a subsequent flood were to take place) [9].…”
Section: Introductionmentioning
confidence: 99%